A Distributed Task Allocation Strategy for Collaborative Applications in Cluster-Based Wireless Sensor Networks. (5th June 2014) - Wang, Feng; Han, Guangjie; Jiang, Jinfang; Qiu, Hao
Abstract : Balancing energy consumption and prolonging network lifetime have been hot topics in energy limited wireless sensor networks (WSNs). It is generally known that multiple sensor nodes collaborating with each other to perform tasks are an important means of energy balancing. In addition, a reasonable task allocation strategy is also an efficient method for task performing and energy saving. Furthermore, in order to save energy consumption, many WSNs are organized into clusters. Therefore, in this paper, we propose a distributed task allocation strategy for collaborative applications (DTAC) in cluster-based WSNs. In DTAC, the service abilities of sensor nodes are first evaluated and then the sensor nodes are classified into different ranking domains. Based on the service abilities of cluster members, the service ability of each cluster is calculated. A complex task can be first allocated to several clusters, and then scheduled on collaborative cluster members. Simulation results demonstrate that, compared with current related works, DTAC is much more efficient for complex task processing in terms of reducing energy consumption, shortening execution time, and balancing network loads.